All Stories Are True : History, Myth, and Trauma in the Work of John Edgar Wideman - Guzzio, Tracie Church (Book collections on Project MUSE., 2011)
Tracie Church Guzzio provides a full-length study of John Edgar Wideman's entire oeuvre to date. Specifically, she examines the ways in which Wideman engages with three crucial themes - history, myth, and trauma - throughout his career, showing how they intertwine. The book argues that, for four decades, the influential African American writer has endeavoured to create a version of the African American experience that runs counter to mainstream interpretations, using history and myth to confront and then heal the trauma caused by slavery and racism.